The Influence Of Road Geometry On The Central Government Policy For The Trans Papua Road Segment Iv Jayapura–Elelim–Wamena - Mexan Andry Rumagit; Bahtiar Bahtiar; Dewi Ana Rusim; Mujiati Mujiati; Bernathius Julison (Journal of Social Research, 2025)
The Trans Papua road network spans 3,259.45 km, comprising 58.24% national roads (1,898.32 km) and 41.76% strategic roads (1,361.13 km). A specific issue arises on the Trans Papua Segment IV (Jayapura–Elelim–Wamena), where the geometric design of the road does not align with the standards set in the Ministry of Public Works and Housing Regulation No. 5 of 2023 regarding technical requirements for road design. This non-compliance poses risks of traffic accidents and impacts travel time, particularly for essential vehicles like fuel supply trucks, which cannot navigate certain segments due to the road's steep gradient (overgrade). This study aims to analyze the compliance of the geometric design on the Jayapura–Elelim–Wamena road segment with the established technical standards and its alignment with the central government's policy to enhance the local economy and ensure equitable pricing in mountainous regions. The research findings reveal that while road handling in Segment IV Jayapura–Elelim–Wamena has been managed by the BPJN Jayapura and BPJN Wamena, the existing geometric conditions do not meet the requirements of Permen PUPR No. 5 of 2023. The current policy focuses on maintaining the functionality of the road through preservation work packages rather than addressing the design deficiencies. This study underscores the need for more comprehensive upgrades to meet regulatory standards for safe and efficient road use.